Dysregulated levels of proangiogenic proteins in the placentas of children with autism spectrum disorder and attention-deficit hyperactivity disorder - Celis, Cristian; Troncoso, Felipe; López, Eduardo; Escudero-Guevara, Esthefanny; Acurio, Jesenia; Escudero, Carlos (Frontiers in Medicine, 2025)
Placental vascularization may influence fetal brain development, but its long-term impact on neurodevelopment remains unclear. In this pilot study, we analyzed two ligand proteins: vascular endothelial growth factor (VEGF) and placental growth factor (PLGF), and their receptors mRNA and protein levels in placentas from children who later were diagnosed with autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), or controls. ASD placentas showed lower VEGF, PLGF, and KDR protein levels but higher FLT1, while ADHD placentas had increased FLT1 and reduced VEGF mRNA. These findings suggest distinct placental vascular alterations in ASD and ADHD, highlighting a potential role of the placenta-brain axis in neurodevelopmental disorders and early-life mechanisms underlying impaired brain development.